2019
DOI: 10.2306/scienceasia1513-1874.2019.45.159
|View full text |Cite
|
Sign up to set email alerts
|

2D and 3D pore structure characterization of bi-layered porous polyethylene barrier membrane using SEM and micro-CT

Abstract: Barrier membrane is an essential component in guided bone regeneration for successful bone augmentation in implant dentistry. The microstructure of barrier membrane can remarkably impact its mechanical properties and biological performances. This study was aimed to investigate the pore structures of a bi-layered porous polyethylene (PPE) barrier membrane by 2D and 3D characterization techniques. Two opposite sides of PPE barrier membrane were imaged with scanning electron microscope and micro-computed tomograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 37 publications
(60 reference statements)
0
7
0
Order By: Relevance
“…Alternative materials are continuing to be developed to improve their properties at a lower cost. Novel B‐PPM used in this study contained two layers with different pore sizes and porosity which were suitable for both rapid fibrovascularization and facilitated new bone formation 12,13,15,35 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternative materials are continuing to be developed to improve their properties at a lower cost. Novel B‐PPM used in this study contained two layers with different pore sizes and porosity which were suitable for both rapid fibrovascularization and facilitated new bone formation 12,13,15,35 …”
Section: Discussionmentioning
confidence: 99%
“…B‐PPM was prepared as described previously 15 . One side of the membrane contained higher porosity with the pore sizes ranging from 140 to 830 mm to facilitate osteoblast proliferation while the other side was designed with less porosity and lower pore size to prevent epithelial cell penetration (Figure 2).…”
Section: Methodsmentioning
confidence: 99%
“…From the clinical perspective, in this study, the tight soft tissue adhesion and attachment to PPE membrane observed at re-entry indicate its good biocompatibility and tissue integration that in turn enhance postoperative membrane stability. This feature may be attributed to the specific 2D and 3D pore microstructures characterized previously [22]. These pores not only facilitate transmembrane transport of blood supply, nutrients, oxygen, and thus bone regeneration, but also enable cell occlusiveness.…”
Section: Discussionmentioning
confidence: 67%
“…The PPE membrane was prepared as described previously [21,22]. Briefly, the mixture of high-density polyethylene (Thaizex 7000F, Bangkok Polyethylene Co., Ltd., Bangkok, Thailand), maltodextrin (Shandong Duqing, Inc., Heze, P. R. China), and polyvinyl alcohol (Sigma-Aldrich Inc., Natick, MA, USA), was prepared at a ratio of 70:20:10 w/w.…”
Section: Ppe Membrane Preparationmentioning
confidence: 99%
See 1 more Smart Citation